UCOMB-real life data: treatment strategies for chronic urticaria patients with comorbidities - Petra Staubach; Benedikt Bilo; Joachim W. Fluhr; Karoline Krause; Kanokvalai Kulthanan; Andac Salman; Connie Katelaris; Jonathan A. Bernstein; Marcus Maurer; Caroline Mann (Taylor & Francis Group, 2024)
AbstractBackground There is a lack of real-life safety data on treatment options for chronic urticaria in the presence of comedication and comorbidities.Methods We present a single-center UCARE pilot study of 212 outpatients with chronic urticaria. Patients were divided into three groups according to different CU therapies according to international guidelines.Results Of 212 patients, 108 (mean age 48.9 years, 71.3% female) had 59 comorbidities, including cardiovascular, autoimmune and malignant diseases. Patients were followed for a mean of 24.6 months (SD ± 21.3). Urticaria therapies were divided into three groups: A: 105 (97.2%) with omalizumab and 2nd generation antihistamines), B: 16 patients (14.8%): dual therapy with antihistamines and cyclosporine in 10 (9.3%), montelukast in five (4. 6%), dapsone in four (3.7%), hydroxychloroquine in one patient (0.9%), C: 12 (11.1%) patients received a third drug for 4.9 months (SD ± 3.2) and one quadruple therapy (2.1 months). 10 out of 12 (83.3%) patients received montelukast, two (16.7%) cyclosporine, two (16.7%) dapsone and one (8.3%) hydroxychloroquine as a third drug for chronic urticaria.Conclusions Combining treatment modalities for chronic urticaria and comorbidities are available and feasible with a good safety profile.